Do medical students receive training in correct use of personal protective equipment?. Issue 1 (1st January 2017) - John, Amrita; Tomas, Myreen E.; Hari, Aditya; Wilson, Brigid M.; Donskey, Curtis J.
ABSTRACT: Background: Healthcare personnel often use incorrect technique for donning and doffing of personal protective equipment (PPE). Objective: We tested the hypothesis that medical students receive insufficient training on correct methods for donning and doffing PPE. Methods: We conducted a cross-sectional survey of medical students on clinical rotations at two teaching hospitals to determine the type of training they received in PPE technique. The students performed simulations of contaminated PPE removal with fluorescent lotion on gloves and were assessed for correct PPE technique and skin and/or clothing contamination. To obtain additional information on PPE training during medical education, residents, fellows, and attending physicians completed written questionnaires on PPE training received during medical school and on knowledge of PPE protocols recommended by the Centers for Disease Control and Prevention. Results: Of 27 medical students surveyed, only 11 (41%) reported receiving PPE training, and none had received training requiring demonstration of proficiency. During simulations, 25 of 27 (92.5%) students had one or more lapses in technique and 12 (44%) contaminated their skin with fluorescent lotion. For 100 residents, fellows and attending physicians representing 67 different medical schools, only 53% reported receiving training in use of PPE and only 39% selected correct donning and doffing sequence. Conclusions: Our findings suggest that there is a need for development of effective strategies to train medical students in correct use of PPE. Abbreviations: PPE: Personal protective equipment; MRSA: Methicillin-resistant Staphylococcus aureus ; SARS: Severe acute respiratory syndrome; MERS: Middle East respiratory syndrome; WHO: World Health Organization; CDC: Centers for Disease Control and Prevention; OSCE: Objective structured clinical examination